If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -1x = -2 Solving -7 + -1x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = -2 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = -2 + 7 -1x = -2 + 7 Combine like terms: -2 + 7 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| 5(x+5)+11=8x-3(x-4) | | 0.3x-0.7x+2=-8 | | 2[10-3(4-2)]+1= | | x^2+3x=2x-3 | | -3+3(6z-2)=-7(2z-2)+2 | | .2x=-1 | | 3x+12=x+14 | | 10p-2(3p-6)=4(3p-6)-8 | | 5x+3=y | | 9(n-3.2)=2(n+0.3) | | X-16=9x | | 26x^2+120x+150=8x^2 | | 8(3x-1)=4(6x+2) | | 0.3-0.7x+2=-8 | | 2=4(x-4)-(x-9) | | 5=-p-12 | | 2(v-1)+4=14 | | 7x+2=x+14 | | 2+3[1+2(4+1)]= | | 6(-y+4)-3(2y-3)=-y+5+5y | | 5p-26=18p | | (c+4)3-6c=2(4-2c) | | 7x+5=-51 | | Hyits=a | | 6m=60 | | 24-2[5-(3*1)]= | | 3=5+3t | | 2x-8=12+3x | | 4x+18-6x+38= | | 0=2t^2-13t+21 | | k+5=4k-10 | | -2x+4=-14 |